Estudio y diseño del sistema de agua potable, alcantarillado sanitario y pluvial de las lotizaciones: Las Morenitas, Los Laureles y 25 de Julio del cantón Santa Rosa, provincia de El Oro. - Segarra Torres, Karla Astrid (2015)
The study design is presented below is intended to provide the most favorable solution to the uncertain scenario of lack of services which are victims the inhabitants of these sectors. It is indivisible and imprescriptible research especially if it involves adequate sanitation, due to diseases caused by lack of supply of treated drinking water and wastewater discharge, thus projecting the increased rate of long-term mortality. The rules governing these studies are in the ability to improve and provide quality public services, availability to have an acceptable quality of water, drainage and adequate treatment of wastewater to reduce enteric diseases in accordance with the provisions by Design Standards. Basically with regard to the technical, geological, hydrological, topographical, safety, functionality and cost are kept, to achieve a good structural design and quality oriented approach of physical-chemical and bacteriological aspects of water . If only we are dedicated to be spectators of such a situation, it is seriously threatening this and to future generations, we need to put a stop to the indolence of the important things and contribute to the welfare and development of these sectors.